Concomitant herpes simplex virus and cytomegalovirus endotheliitis in immunocompetent patient - Kasetsuwan,N. (BMJ Publishing Group, 2015)
A case of an immunocompetent 51-year-old healthy man with chronic recurrent disciform corneal oedema and hypertensive anterior uveitis in the right eye for 2 years was unresponsive to topical corticosteroid and systemic acyclovir. Diagnostic anterior chamber tapping was performed and viral DNA PCR was positive for both cytomegalovirus and herpes simplex virus. The patient was treated with both oral valganciclovir for 3 months and long-term oral acyclovir. His condition improved significantly after the treatment; intraocular pressure and anterior chamber inflammation were controlled and the remaining keratic precipitates in the cornea started to clear up. Copyright 2013 BMJ Publishing Group. All rights reserved.